How Clinical Practice Research Datalink data are used to support pharmacovigilance - Rebecca E. Ghosh; Elizabeth Crellin; Sue Beatty; Katherine Donegan; Puja Myles; Rachael Williams (SAGE Publishing, 2019)
Pharmacovigilance can be defined as the science of monitoring medicines and vaccines after license for use, the purpose of which is to quantify and characterise the safety profile of a medicine, identify previously unknown adverse reactions, inform risk-benefit assessment, and support the development of actions that can be taken to reduce risks, optimise benefits and monitor their effectiveness. This review discusses the Clinical Practice Research Datalink (CPRD), which is the source of the largest research database in the UK with longitudinal, representative primary care data linked to data from other healthcare settings. CPRD supports international pharmacovigilance by providing a large, anonymised representative general population database with comprehensive capture of patient risk factors and outcomes to researchers within academic, regulatory and pharmaceutical organisations. The specific advantages of CPRD data are discussed in the context of the 'six Vs of big data' including volume, velocity, variety, veracity, validity and value. Examples of where CPRD data have been used for pharmacovigilance research and how these have fed into guidelines and policy are discussed.